2023
DOI: 10.15174/au.2023.3558
|View full text |Cite
|
Sign up to set email alerts
|

Valoración nutricional y fermentación in vitro de mezclas de follaje de árboles con harina de yuca en dietas para borregos

Abstract: El objetivo del estudio fue evaluar el valor nutricional de dietas de Panicum maximum suplementadas con 30% de follajes arbóreos mezclados con yuca (Manihot esculenta). Se compararon seis tratamientos: T0 (P. maximum), T1 (Leucaena leucocephala), T2 (Moringa oleifera), T3 (Tithonia diversifolia), T4 (Guazuma ulmifolia) y T5 (Hibiscus rosa-sinensis). Se determinó la composición química, fermentación y digestibilidad in vitro, así como la producción de ácidos grasos volátiles (AGV). Los datos se analizaron con u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…CSD may have had a higher content of fermentable starch (a result of silage) than DEN10 and DEN20, which have fewer starch sources; including cactus silage tends to decrease MFF [15]. However, the MFF values of the present research were similar to previous ones when evaluating diets with cassava [28] and hibiscus [24]. The SFF was higher in DWS and CSD compared to DEN10 and DEN20 (P0.05).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…CSD may have had a higher content of fermentable starch (a result of silage) than DEN10 and DEN20, which have fewer starch sources; including cactus silage tends to decrease MFF [15]. However, the MFF values of the present research were similar to previous ones when evaluating diets with cassava [28] and hibiscus [24]. The SFF was higher in DWS and CSD compared to DEN10 and DEN20 (P0.05).…”
Section: Resultssupporting
confidence: 71%
“…The FFF was different between diets (P0.002). Although previously studies reported similar values [15], [28], it increased as cactus silage in the diet increased (P0.05), suggesting higher nonstructural carbohydrate content (NSC) previously related to the FFF [29].…”
Section: Resultsmentioning
confidence: 59%